Structural model of life satisfaction based on personality traits with the mediating role of emotion regulation in paramedical students - Afsane Samadpor; Sadrollah Khosravi; Mahbobeh Chinaveh (Shahid Beheshti University of Medical Sciences, 2021)
Introduction: Experiencing happiness and life satisfaction is the ultimate goal of human beings in life. The aim of this study was to investigate structural model of life satisfaction based on personality traits with the mediating role of emotion regulation in paramedical students Methods: The statistical population of the study included all students of the paramedical school of Shiraz, from which 486 people were selected by convenient sampling methods. Neo, Life Satisfaction and Emotion regulation Questionnaires were used to collect research data. The evaluation of the proposed model was done through Structural Equation Modeling (SEM) using SPSS software (version 18) and AMOS (version 18). Bootstrap method was used to test the indirect effects in the proposed model. Results: The results showed that the proposed model has a relatively good fitness with the data. Better fit was achieved by eliminating two non-significant paths. Conclusion: According to the research results, emotion regulation has a mediating role in relation to personality traits and life satisfaction, so it may be possible to include management and emotion regulation training programs to increase life satisfaction among social prevention programs.